161k views
17 votes
Complete the square x^2+6x=-2

User Bolanle
by
5.8k points

1 Answer

6 votes

Answer:

Explanation:

Answer this by inserting a positive number between the '6x' and the '=' sign and then subtracting the same number:

x^2 + 6x + 9 - 9 = -2

Where does the "9" come from? Take half the coefficient of x (which is 6) and square the result (obtaining 36). Now add 36 after the "6x" and then subtract 36:

x^2 + 6x + 9 = 7

Rewrite this with a perfect square on the left side:

(x + 3)^2 = 7 Here we have successfully "completed the square."

User Leonardo Costa
by
5.1k points